(untitled) (Academicia Globe: Inderscience Research, 2022)
This article at present, there is a problem of finding new factors that will ensure the sustainable development of the national economy in order to ensure the financial stability of the agro-industrial complex, increase its competitiveness. One way to solve this problem is to update the production management system with a cluster approach, which increases the efficiency of economic activity.